(3GdhLhg hGdfXGFQ aj GdbQBf GdYXjes - (3ebGJd Hf SdjeGf Hf HTjQ GdCROj, CHh GdMSf,J (B150 (3g` s ((3YHO GdQMef Hf YKeGf Hf eMehO GdOeTbi s)
(3ChdgG (B:s
(3MOK GHh UdM GdgPjd Hf MHjH , YR ebGJd Hf SdjeGf , hYeGQ Hf CHj YGeQ Yf CHjg jQaYg Edi GdfHi Udi Gddg Ydjg hSde bGd dG jchf GdQLd abjgG cd Gdabg MJi jQi ddbQBf hLhgkG cKjQg s
(3BNQgG (B:s
(3hEfG ahbge bGgQhf (B: (3jYfi SdWGf hCeQi ahb SdWGfge aCbgQge HPdc Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B317s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs